Original article Increased reactive oxygen species (ROS) production and low catalase level in fibroblasts of a girl with MEGDEL association (Leigh syndrome, deafness, 3-methylglutaconic aciduria) - Karkucinska-Wieckowska, Agnieszka; Lebiedzinska, Magdalena; Jurkiewicz, Elzbieta; Pajdowska, Magdalena; Trubicka, Joanna; Szymanska-Debinska, Tamara; Suski, Jan; Pinton, Paolo; Duszynski, Jerzy; Pronicki, Maciej; Wieckowski, Mariusz R.; Pronicka, Ewa (Folia Neuropathologica, 2011)
Association of 3-methylglutaconic aciduria (3-MGCA) with sensorineural deafness and Leigh-like encephalopathy (MEGDEL) was described as a very rare mitochondrial disorder without a known molecular background. We present clinical and biochemical characteristics of a 4.5-year-old girl with a similar association. The clinical course of the disease was as follows: in the neonatal period transient adaptation troubles; at 4-5 mo failure to thrive and hypotonia; at 13 mo: extrapyramidal symptoms, sensorineural deafness, Leigh syndrome on MRI, pigmentary degeneration of retina, episodes of respiratory alkalosis, increased lactate in plasma, urine and brain, and increased excretion of 3-MGCA. Mitochondrial encephalopathy was suspected and muscle biopsy performed. Only mild lipid accumulation was found by muscle histopathology and histochemistry. Unspecific decrease of respiratory chain complexes was revealed by muscle homogenate spectrophotometry. The in-gel activity assay in the patient’s muscle confirmed a combined defect of OXPHOS, particularly indicating suppression of mitochondrial ATP synthase (complex V) activity. Measurements of functional mitochondrial bioenergetic parameters in the patient’s fibroblasts revealed a decrease in the mitochondrial membrane potential and activity of the mitochondrial respiratory chain. At the same time, a significant increase of ROS production (cytosolic and mitochondrial superoxide and H 2 O2) with signs of protein damage (protein carbonylation), and decreased antioxidant defence (SOD1 and SOD2) were observed. Additionally, the catalase amount was surprisingly low in comparison with healthy control and other reference 3-MGCA cases (Barth syndrome). Conclusion: (1) the natural history of the disease in the presented patient confirms the existence of previously reported clinical phenotype of MEGDEL (2) antioxidant defence impairment due to abnormal catalase metabolism/transport may characterize an unknown basic defect which led to the development of MEGDEL association.